Flow and heat transfer inside a new diversion-type gas heating device. (2nd July 2016) - Guo, Yun; Guo, Zhixiong
ABSTRACT: The present paper characterizes ethylene glycol flow and heat transfer inside a new diversion-type gas heating device. A two-dimensional (2-D) natural convection heat transfer model was built and solved by the finite volume method with unstructured body-fitted grids. The numerical model was first validated through temperature comparison with the experimental measurements in a conventional device structure. Then analyses and comparisons of the flow fields and temperature distributions with use of different guide plate structures were carried out. The numerical results show that using the guide plate structures can form better organized flow patterns that augment heat transfer. The heat required for heating up the gas passing through the heating device can be reduced by 3% via installing two guide plates.